Association Between D-dimer and Early Adverse Events in Patients With Acute Type A Aortic Dissection Undergoing Arch Replacement and the Frozen Elephant Trunk Implantation: A Retrospective Cohort Study - Liu, Tong; Zheng, Jun; Zhang, You-Cong; Zhu, Kai; Gao, Hui-Qiang; Zhang, Kai; Jin, Xiu-Feng; Xu, Shang-Dong (Frontiers in Physiology, 2020)
Objective: In the present study, we investigated the associations between D-dimer levels at admission and early adverse events in patients with acute type A aortic dissection undergoing arch replacement and the frozen elephant trunk (FET). Methods: We retrospectively analyzed data of patients with acute type A aortic dissection undergoing aortic arch surgery and FET from July 2017 to December 2018 at Beijing Anzhen Hospital. D-dimer levels were evaluated within 24 hours of admission. Multivariate Cox regression analysis was used to determine independent predictors of early postoperative adverse events. Results: A total of 347 patients were included in the study. The average age of the patients was 48.07 ± 10.56 years, with male predominance (79.25%). The incidence of 90-day postoperative adverse events was 18.7%, consisting of 14.7% mortality and 4.0% permanent neurological dysfunction. The median D-dimer level was 1.95 ug/ml (interquartile range, 0.77-3.16 ug/ml). Multivariable Cox regression analysis revealed that D-dimer level was independently associated with 90-day postoperative adverse events after adjustment for confounding factors (hazard ratio=1.19 per 10 ug/ml increase in D-dimer, 95% confidence interval: 1.01-1.41; P =0.039). Kaplan–Meier analysis revealed that the highest tertile (median 6.27 ug/ml) had more 90-day postoperative adverse events compared with the median and lowest tertiles (P=0.0014). Sub-analysis found that the association remained unchanged. Conclusion: Increased D-dimer levels at admission were associated with 90-day postoperative adverse events in patients with acute type A aortic dissection undergoing arch replacement and FET. These results may help clinicians optimize the risk evaluation and perioperative clinical management to reduce early adverse events.